Effect of growth temperature on the terahertz-frequency conductivity of the epitaxial transparent conducting spinel NiCo2O4 films - Chia, Elbert E. M. (2014)
We have measured the terahertz-frequency optical conductivity of the epitaxial inverse spinel NiCo2O4 films grown at different temperatures. The low-temperature-grown film exhibits a metallic behavior with ferrimagnetic ordering, while the high-temperature-grown film shows greatly suppressed magnetization and insulating behavior. Both films exhibit band-like coherent conduction at intermediate temperatures, albeit with very different carrier densities consistent with the proposed models of cation valencies in this mixed-valence material. Both films also display a crossover to incoherent transport at low temperatures, indicating a disorder-induced tendency toward localization.